Histological Study of the Effect of Isoxicam on Ovary of Albino Mice Mus Musculus (Indian Journal of Forensic Medicine & Toxicology, 2020)
Non-Steroidal Anti Inflammatory Drugs (NSAIDs) are the most prescription as therapeutic drugs, used to treat of rheumatic diseases, due to analgesic, antipyretic and anti-inflammatory activity. Isoxicam is a member of NSAIDs group use to stop inflammation, pain associated with arthritis, osteoarthritis, ankylosing and spondylitis. The goal of the present study is to revealed the effect of different doses of Isoxicam on ovaries tissue in mice. Twenty four female mice are randomly divided into control (n = 6) and experimental (n=18) groups. The experimental groups are subdivides into three groups . Each administrated by (0.0714, 0.1428, 0.71428)mg/kg/day for twenty days, respectively; however the control group just injected by distill water. In twenty day, mice were killed and ovaries tissue was prepared for light microscopic examination. All the experimental animals were injected by drug revealed a hyperplasia of germinal cells on the surface of ovary, tongue like projection of primordial oocytes extend to the medulla, multiple oocytes with disarrangement of follicles and deficient of follicular fluid associated with disappearance of oocytes, vacuolation in the cortical layer of the ovary, compressed premature follicle, hypercellularity of follicular cells, degeneration of germinal layer of cortex surface and hyperplasia of primordial oocytes, therefore it is recommended that using of this drug have many side adverse on female fertility.
Keywords: Histological , Isoxicam , ovary , albino mice .